THE INTERDECADAL VARIABILITY OF ADVANCE AND RETREAT OF EAST ASIAN SUMMER MONSOON AND THEIR EFFECT ON THE REGIONAL RAINFALL OVER CHINA - 吕心艳 张秀芝 陈锦年 (Journal of Tropical Meteorology, 2013)
The daily precipitation data of 740 stations in China(1958–2001)and the daily upper air data of European Centre for Medium-Range Weather Forecasts reanalysis dataset(1958–2001)are used to define an East Asian summer monsoon(EASM)index based on dynamic and thermal factors.The index is used to represent the front(or leading edge)of EASM to describe and characterize the advance and retreat of EASM objectively.During 1958–2001,the EASM movement underwent three interdecadal abrupt shifts in 1965,1980 and 1994,respectively.During 1958–1964,the front primarily concentrated in South China and North China,while it stayed at the mid-and lower-Yangtze River for a short period.During 1965–1979,the front was located in South China and the lower reach of Yellow River for a long time.During 1980–1993,the time in which the front of EASM stayed at the mid-and lower-Yangtze River was much longer,but it settled in North China for just a short time.During 1994–2001,the front generally concentrated in the south of the mid-and lower-Yangtze River.The three interdecadal shifts of EASM directly resulted in rainfall anomalies,as well as frequent disasters of flood and drought in East China.